Implementation of Teacher Attendance Monitoring Application at SMK Ibnu Sina Batam - Arifin, Nofri Yudi; Suri, Ghea Paulina; Johan, Dasman; Veza, Okta; Larisang, Larisang (Journal of Information System, Technology and Engineering, 2024)
This study aims to analyze and design a web-based teacher attendance monitoring application at SMK Ibnu Sina Batam. We expect this application to enhance the efficiency and effectiveness of teacher attendance management through the use of digital technology. The research methods used include literature studies, interviews, and direct observation of the teacher attendance management process. We design the system using the Unified Modeling Language (UML), implement it using the CodeIgniter framework, and use MySQL as its database. We conduct testing using the Black Box method to verify that all functions operate as anticipated. The results show that this application can monitor teacher attendance in real-time and improve discipline. By cutting down on manual checks and enhancing transparency and accountability in school management, the implementation of this application significantly enhances the quality of education at SMK Ibnu Sina Batam.